KEKERASAN DALAM MEDIA MASSA SEBAGAI CONTOH BENTUK PENDIDIKAN DISKRIMINATIF TERHADAP PEREMPUAN - mu’awanah, M.Pd, Hj. Elfi (EGALITA, 2008)
Violence on mass media is one short of discrimination towards women. It shows the fact that violence which are mostly women experiencing needs real solution such as gender issues and regulation on domestic violence socialization. Government plays important part in reducing the rate of domestic violence  that are presented in mass media lately in terms of law enforcement. It is also  crucial that all people are aware of this issue  if they become the victims report to institution or person who is in charge with domestic violence case.